Sensitivity of sand lance to shifting prey and hydrography indicates forthcoming change to the northeast US shelf forage fish complex. (26th January 2021) - Suca, Justin J; Wiley, David N; Silva, Tammy L; Robuck, Anna R; Richardson, David E; Glancy, Sarah G; Clancey, Emily; Giandonato, Teresa; Solow, Andrew R; Thompson, Michael A; Hong, Peter; Baumann, Hannes; et al.
Abstract: Northern sand lance ( Ammodytes dubius ) and Atlantic herring ( Clupea harengus ) represent the dominant lipid-rich forage fish species throughout the Northeast US shelf and are critical prey for numerous top predators. However, unlike Atlantic herring, there is little research on sand lance or information about drivers of their abundance. We use intra-annual measurements of sand lance diet, growth, and condition to explain annual variability in sand lance abundance on the Northeast US Shelf. Our observations indicate that northern sand lance feed, grow, and accumulate lipids in the late winter through summer, predominantly consuming the copepod Calanus finmarchicus . Sand lance then cease feeding, utilize lipids, and begin gonad development in the fall. We show that the abundance of C. finmarchicus influences sand lance parental condition and recruitment. Atlantic herring can mute this effect through intra-guild predation. Hydrography further impacts sand lance abundance as increases in warm slope water decrease overwinter survival of reproductive adults. The predicted changes to these drivers indicate that sand lance will no longer be able to fill the role of lipid-rich forage during times of low Atlantic herring abundance—changing the Northeast US shelf forage fish complex by the end of the century.